2018
DOI: 10.1109/tvt.2017.2771531
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum Efficient MIMO-FBMC System Using Filter Output Truncation

Abstract: Abstract-Due to the use of an appropriately designed pulse shaping prototype filter, filter bank multicarrier (FBMC) system can achieve low out of band (OoB) emissions and is also robust to the channel and synchronization errors. However, it comes at a cost of long filter tails which may reduce the spectral efficiency significantly when the block size is small. Filter output truncation (FOT) can reduce the overhead by discarding the filter tails but may also significantly destroy the orthogonality of FBMC syst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…In this section, numerical simulations are given to validate the proposed schemes. In our simulations, we consider an FBMC/OQAM system with 2048 subcarriers, in which the IOTA function is taken as the pulse-shaping filter [15]. Note that only a partial frequency band, i.e., 180 subcarriers is assigned for one user to achieve channel measurement and noise estimation.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, numerical simulations are given to validate the proposed schemes. In our simulations, we consider an FBMC/OQAM system with 2048 subcarriers, in which the IOTA function is taken as the pulse-shaping filter [15]. Note that only a partial frequency band, i.e., 180 subcarriers is assigned for one user to achieve channel measurement and noise estimation.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…only depends on the filter g½k and the timefrequency position ðm, nÞ. Note that the pulse-shaping filter g½k in FBMC/OQAM is real-valued and symmetric [15,16]. Due to the fact that g½k is real-valued and symmetric, it can be easily demonstrated that the following equations hold…”
Section: Analysis Of Imaginary Interferencementioning
confidence: 99%
“…It can be seen from (12), that the transmitted symbol vector s m is accompanied with interference terms caused by the multipath channel and noise. In this section we estimate the interference and noise power in the FBMC/QAM-IM system.…”
Section: Interference and Noise Power Estimationmentioning
confidence: 99%
“…FBMC scheme has some obvious advantages for VRs. Compared with OFDM, FBMC offers higher throughput because of no Cyclic Prefix (CP); however, FBMC also introduces long filter tails which may reduce the spectral efficiency significantly when the block size is small 26 . Due to this reason, FBMC is better suited for higher bandwidth services that utilize larger block sizes.…”
Section: Introductionmentioning
confidence: 99%